Analisis Kompetensi Manajerial Jabatan Pelaksana di Balai Pendidikan dan Latihan Keagamaan Semarang - Rukhana Fitriati; Retno Sunu Astuti; Budi Puspo Priyadi; Teuku Afrizal (PERSPEKTIF, 2021)
The merit system is defined as human resource management based on work performance, competence is a major factor in improving work performance, competence is indispensable in every job both in the private sector and in the government sector, in the government sector, work related to community service is directly carried out by an executive position Therefore, an executive position must have a minimum competency, namely managerial competence. The purpose of this study was to analyze managerial competence, inhibiting factors faced by executors who work at the Semarang Religious Education and Training Center. The research method used is descriptive quantitative with a survey approach to answer the research objectives, namely to analyze the managerial competence of the executive positions and to analyze the inhibiting factors faced by executive positions who work at the Semarang Religious Training Center. The results showed that the managerial competence of the executive positions who worked at the Semarang Religious Education and Training Center was in the medium category and the inhibiting factor was the lack of competency development in increasing knowledge. Recommendations as steps that must be taken by the Semarang Religious Education and Training Center are to increase the competency development of executive positions.